Determinan of value the company impact on Employee Stock Option Plan & Free Cash Flow : Coal Mining Market Survey for the Years 2016-2020 - Devi Iriandha Widyastuti; Ria Dini Apriliasari; Ratna Agustina; Anna Kridaningsih (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2023)
The observed worth of a firm by investors is frequently correlated with stock prices; the higher the stock price, the greater the business value. The percentage of stockholder return on investment represented by firm worth is important. Investors will be overjoyed if they rarely obtain a higher rate of return on their investment. More investors are ready to engage in a company with a higher value. In order to determine how Employee Stock Option Plans and Free Cash Flow Affect a Company's Value, this study will be conducted. The results of this research, which looked at the financial records of each firm using 45 data sets from 2016 to 2020, revealed that the awarding of ESOP and FCF had a significant effect on the company's performance. The ESOP and FCF were created with the goal of aligning the interests of workers (agents) and owners (principals), thereby decreasing conflicts of interest between agents and principals. Because as employee success improves, so does the company's performance. According to the study's findings, ESOP and FCF have a substantial impact on company value.